Market Capitalization, Leverage, and the Pursuit of Sustainable Growth: Evidence from the Indonesian FinTech Industry - Iwan Suhardjo; Meiliana Suparman; Yulias Hidayah; Misnawati Misnawati; Adinda Nurul Rahmadyan; Rendy Diaz Hirlian (Jurnal Akademi Akuntansi, 2024)
Purpose: This research aims to analyze the influence of three crucial financial factors in companies, namely Board Education Background Accounting, Market Capitalization, and Leverage on the Sustainable Growth Rate (SGR). Methodology/approach: The type of research used in this study is quantitative research with an associative causal approach. The analyzed data consists of financial technology banks in Indonesia from 2017 to 2022, along with data from conventional companies to compare the performance of both types of banks.  The number of companies used is six FinTech and four conventional banks that compare the performance of the two types of samples. Findings: The research results provide valuable insights for FinTech stakeholders, assisting in making informed decisions regarding financial management and growth strategies. Practical and Theoretical contribution / Originality: This research contributes to the academic literature in the field of corporate finance and sustainable growth, especially within the rapidly evolving FinTech context. Research Limitation: Despite the fact that this study considers three main variables, there is still a possibility that other factors influencing the SGR are not taken into account.